Policy-making in the European Union - Wallace, Helen (Helen S.).; Pollack, Mark A. 1966-.; Young, Alasdair R. (Oxford New York Oxford University Press, 2010)
"The policies of the European Union profoundly affect the lives of people in Europe and around the world. The new edition of this highly successful textbook outlines how and why such decisions are made, as well as the key challenges faced by policy-makers in the current political and economic climate. Policy-Making in the European Union begins by clarifying the institutional framework of the EU and the analytical approaches used to understand it. A wide range of crucial and illustrative policies are then explored in detail by subject experts. This volume includes new chapters on ways of analyzing the EU's policy process and on energy policy. A central theme to the volume is how the recent expansion to twenty-seven member states has affected policy-making across the different policy sectors. The conclusion reflects on how this challenge and the protracted constitutional stalemate have affected policy-making in the EU. It also explores the impact of the financial and economic crises that have struck Europe over the past several years. The sixth edition is fully up-to-date, and is the ideal text for all those with an interest in the policy-making of the European Union"--Provided by publisher.
Machine generated contents note: -- Part One: Institutions, Process and Analytical Approaches -- 1. Overview, Mark A. Pollack, Helen Wallace, and Alasdair R.Young -- 2. Theorizing EU Policy-Making, Mark A. Pollack -- 3. The European Policy Process in Comparative Perspective, Alasdair R. Young -- 4. An Institutional Anatomy and Five Policy Modes, Helen Wallace -- Part Two: Policies -- 5. The Single Market, Alasdair R.Young -- 6. Competition Policy, Stephen Wilks -- 7. Economic and Monetary Union, Dermot Hodson -- 8. The Common Agricultural Policy, Christilla Roederer-Rynnning -- 9. The Budget, Brigid Laffan and Johannes Linder -- 10. The Structural Funds and Cohesion Policy, David Allen -- 11. Social Policy, Stephan Leibfried -- 12. Employment Policy, Martin Rhodes -- 13. Environmental Policy, Andrea Lenshow -- 14. Biotechnology Policy, Mark A. Pollack and Gregory C. Shaffer -- 15. Energy Policy, David Buchan -- 16. Trade Policy, Stephen Woolcock -- 17. Enlargement, Ulrich Sedelmeier -- 18. Foreign and Security Policy, Bastian Giegerich and William Wallace -- 19. Justice and Home Affairs, Sandra Lavenex -- Part Three: Conclusions -- 20. EU Policy-Making in Challenging Times: Adversity, Adaptability, and Resilience, Mark A. Pollack, Helen Wallace, and Alasdair R. Young.
Includes bibliographical references and index.
Tac-2764g donated by UPAA Netherlands on 03 Dec 2015.
Keywords: European Union; Political planning -- European Union countries